Analysis of the prospectives of intermodal transport and logistics centres in Lithuania - Palšaitis, Ramūnas; Bazaras, Darius (Transport, 2004)
It is identified that the creation of regional logistics centres in Lithuania is one of the main measures of the improvement of transport‐related infrastructure in the country. These centres will be the first public Logistics Centres in Lithuania established according to contemporary requirements and will provide necessary co‐operation with big trading companies and other logistics centres in and outside Europe. Transport Corridors No I and No IX must be very important because Logistics Centres in Lithuania will have a significant impact on the business linked to separate regions and to the whole country. The benefits deriving from an increase of international multimodal transit traffic will be also related to the complementary and boosting activities of logistic services associated with the development of logistics centres network in Lithuania. First Published Online: 27 Oct 2010